ANALISIS DAN PERANCANGAN USER INTERFACE DAN USER EXPERIENCE BNI LIFE MOBILE DENGAN METODE USER CENTERED DESIGN - Jasmin Maula Putri (2022)
PT. BNI Life Insurance or commonly known as BNI Life is an insurance company that provides various products such as life (life) insurance, health, education, investment, pension, and sharia. In carrying out its transactions, BNI Life has an application called BNI Life Mobile to make insurance claims which can be downloaded through the Play Store and App Store. With the BNI Life Mobile application, it is hoped that it will make it easier for customers to claim their products. However, this must be supported by a good, attractive, and easy-to-understand user interface. This study aims to analyze the UI/UX on the BNI Life Mobile application to determine the usability value by applying the User Centered Design (UCD) method. The application of the UCD method is carried out by carrying out questionnaires and prototyping with the System Usability Scale (SUS) technique. This research produces a new interface in the form of a prototype that can be used as a suggestion for BNI Life with an increase in the usability value of 20 so that BNI Life Mobile application users can feel the usability and good experience when using it. Keywords: BNI Life Mobile, Interface, Prototyping, User Centered Design, System Usability Scale